THE USE OF CHILDREN'S SONGS IN LEARNING ENGLISH VOCABULARY IN ELEMENTARY SCHOOL - Rini, Dwi Setya; M.Pd , Yahmun Yahya (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to explore the effectiveness of the use of children's songs in learning English vocabulary in elementary school. The study involved 2nd and 3rd grade students from three primary schools in urban areas. Data was collected through pre-tests and post-tests to measure improvement in vocabulary acquisition, as well as interviews with teachers to gain their perspective on the method. The results showed that the use of children's songs significantly improved students ' mastery of English Vocabulary. Teachers also report that students are more motivated and participate actively in learning when using children's songs. This study suggests the integration of children's songs in the curriculum of English learning in elementary school.